Fabrication of Ethosomes Containing Tocopherol Acetate to Enhance Transdermal Permeation: In Vitro and Ex Vivo Characterizations - Naheed Akhtar; Naveed Akhtar; Farid Menaa; Walaa Alharbi; Fatima Saad Salem Alaryani; Ali Musfer Alqahtani; Faizan Ahmad (Gels, 2022)
Background: Tocopherol acetate (TA) is known as a skin moisturizing and photoprotective agent. One major drawback with tocopherol and its derivatives remains its limited stability. Aim: To develop highly stable TA-containing ethosomal gel (TAEG) as an advanced dosage form. Methods: A cold method technique was used to produce the ethosomes. An in vitro evaluation of viscosity, conductivity, and pH stability was carried out for three months. An in vitro physical characterization of the nanoparticles (NPs) that included particle size (PS), zeta potential (ZP), transmission electron microscopy (TEM), and Fourier-transform infrared (FTIR) spectroscopy analysis was then performed. Organoleptic evaluation, thermostability at 8 °C, 25 °C, 40 °C and 40 °C ± 75% RH, pH, conductivity, viscosity, and spreadability measurements were also performed in vitro for three months. An ex vivo permeation study was performed in phosphate-buffered solution (1× PBS; pH 5.5 or pH 7.4) at 37 ± 0.2 °C by using rat abdominal skin and the Franz diffusion cell method. The data of three independent experiments were expressed as mean ± SD. A two-way ANOVA was applied to compare data on TAEG versus TA control gel (TACG). Results: PS of the ethosomes was in the range of 144–289 nm. A total of nine formulations were developed. Optimized TAEG formulation (TA-5) was selected based on the highest entrapment efficiency (EE) of 99.71%, while the stability, the PS, and the uniformity-based polydispersity index (PDI) were also among the best. TA-5 exhibited smooth spherical ethosomal NPs with PS of 200.6 nm, ZP value of −18.6 V, and PDI of 0.465. Stability data obtained for TA-5 in terms of rheology, conductivity, and pH presented no significant change (p > 0.05) during the entire study duration. Rheological studies indicated that TA-5 followed a non-Newtonian behavior of shear thinning system. The ex vivo drug permeation was 44.55 ± 0.01% in TA-5 and the drug retention in skin was 51.20%, which was significantly higher than TACG as observed after 24 h permeation study (p < 0.05). Conclusions: The newly developed TAEG formulation appears promising to enhance the effectivity of TA and its topical application.